Miss Apple : letters of a Maine teacher in Kentucky - Cunningham, Eleanor W. (1st Books Library, 2002)
In 1998, Eleanor Cunningham found twelve letters which her mother, Ethel V. Applebee, had written to her mother in 1920-21. Ethel was one of thousands of Northern teachers sent to the South by the American Missionary Association to teach black children after the Civil War. The book also includes the love letters between Ethel, and her future husband, Howard Leighton of Cumberland, Maine. Howard Leighton lived in Falmouth when he wrote letters to Ethel, in the house that is now the Falmouth Historical Society museum.
Includes bibliographical references.
Ethel was born in Enfield, Maine, on February 12, 1893. When she was 13 years old her family moved to Bucksport, Maine, where Ethel enrolled in East Maine Conference Seminary and Normal School, graduating in 1911. Her first teaching job was in Easton, Maine. After teaching in the South, marriage to Howard Leighton of Cumberland, Maine, and living in Falmouth, Maine, Howard and Ethel moved to Rockville, Maryland in 1923. Ethel died in 1973 in Olney, Maryland.
Keywords: Applebee, Ethel Valentine; Appleby family; Layton family; Leighton family; Elementary school teachers -- Maine -- Biography; Elementary school teachers -- Kentucky -- Biography; Teachers -- Maine; Schools -- Maine -- Easton; Weddings -- Maine; Love-letters.; Letters; Bucksport (Me.) -- Biography; Cumberland Foreside (Me.) -- Biography; Falmouth (Me.) -- Biography